Konstrukcja i funkcjonowanie sytemu wczesnego ostrzegania opartego na wskaźniku bieżącym płynności finansowej - Szpulak, Aleksandra (Construction and Functioning of Early Warning System Based on Current Liquidity Ratio, 2006)
In this article author presents early warning system that is due to generate early warning signals which predict corporate liquidity problems. The main goal of that system is to support the management of the corporate liquidity. Presentation of that system involves description of its functioning schemes, its early warning procedures and signals definitions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 305-316